ANALISIS PRODUKSI DAN PENDAPATAN BUDIDAYA RUMPUT LAUT DI DESA LALOMBI KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Lagaronda, Indra Setiawan (JSTT, 2016)
This research aims to (1) analyze the influence of production factors against seaweed production at Lalombi Village, Banawa Selatan district of Central Sulawesi Province and (2) analyze income of seaweed cultivation farming at Lalombi Village, Banawa Selatan district of Central Sulawesi Province. The research was conducted at Lalombi village. The method applied was survey and the sample gathered through simple random sampling. The result reveals that (1) seeds number, workers and the long of harvest significantly affect on Î± 1% whereas working capital no real effect to seaweed production and (2) total production of respondents is 49.050 Kg/3.670 m/ planting season with sell price Rp 7.000/Kg dry, then, total of respondents acceptance on seaweed cultivation farming is Rp 343.350.000/3.670 m/ planting season. Total cost of production is Rp 197.181.000/ planting season. Total income obtained by respondents on seaweed cultivation farming Rp 146.169.000/3.670 m/planting season or Rp3.109.999,58/78m/planting season.